Composite diaphragm as well as manufacturing method and application thereof
By using a hydrophilic modified matrix and a self-assembled hybrid crosslinked coating in the lithium-ion battery separator, the problems of insufficient electrolyte wettability and thermal stability are solved, thereby improving the manufacturing efficiency and safety of the battery.
Patent Information
- Application Number
- CN202510980100.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-10-24
AI Technical Summary
Existing lithium-ion battery separators have shortcomings in electrolyte wettability and thermal stability, resulting in long electrolyte injection time, low production efficiency, and easy thermal shrinkage under high temperature conditions, posing safety hazards.
A hydrophilic modified membrane matrix and a self-assembled hybrid cross-linked composite fiber coating, including nanofibers wrapped with apatite nanowires, are used to form a multi-level porous structure, which improves electrolyte wettability and heat resistance, and aramid nanoparticles are added to enhance flame retardancy.
It significantly shortens the electrolyte injection time, improves cell manufacturing efficiency, enhances battery cycle life, strengthens battery safety, prevents electrolyte combustion, and suppresses heat spread.
Smart Images

Figure BDA0005502681630000161 
Figure BDA0005502681630000171 
Figure BDA0005502681630000181
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of batteries, and relates to a composite separator, a manufacturing method thereof and an application thereof. BACKGROUND
[0002] With the optimization of global energy structure and the rapid development of new energy industry, lithium ion batteries have been widely used in power batteries, energy storage systems and consumer electronics due to their high specific energy density, long cycle life, low self-discharge rate and other advantages. Under the promotion of electric vehicles and large-scale energy storage systems, higher requirements are put forward for the energy density, safety, cycle stability and fast charging performance of lithium ion batteries. As one of the core components of lithium ion batteries, the separator not only bears the basic functions of isolating the positive and negative electrodes and preventing short circuit, but also provides a channel for the migration of lithium ions, and is an important physical interface for building a complete charging and discharging circuit. Therefore, the performance of the separator material directly affects the overall electrochemical behavior, thermal stability and safety characteristics of the battery.
[0003] At present, the separator used in commercial lithium ion batteries is mainly based on polyolefin polymers such as polyethylene (PE) and polypropylene (PP), or a composite multi-layer structure (such as PP / PE / PP). These base films are prepared by dry stretching or wet phase separation process, and have good mechanical strength, chemical inertness and moderate porosity, which can meet the basic application requirements under the conventional liquid electrolyte system. However, due to the fact that polyolefin materials belong to non-polar polymers, their surface energy is low, which leads to poor wettability with polar organic carbonate electrolyte. In the liquid injection process, due to the slow absorption rate of the separator to the electrolyte, a long injection time and multiple cycle injection operations are often required, which seriously affects the production efficiency and product yield. In addition, during the long-term cycle use of the battery, especially under high rate or high temperature conditions, due to the difference in liquid retention capacity of each region in the battery, the middle region of the electrode sheet is prone to form a local liquid-poor area first, which further leads to the obstruction of lithium ion transport and the increase of interface impedance, affecting the kinetic performance and service life of the battery.
[0004] In order to improve the electrolyte wettability of the separator, the existing technology usually adopts the method of coating a functional coating on the surface of the base film. It usually includes ceramic coatings formed by (such as Al2O3, SiO2, TiO2) and the like. It is widely used due to its good thermal stability, liquid affinity and certain mechanical support. However, from the perspective of material structure, the base film still accounts for the main proportion of the overall thickness of the separator, and its porosity accounts for a high proportion, so it is difficult to fundamentally change the wettability of the separator body by relying only on the functional coating, and the adsorption capacity and retention capacity of the electrolyte are still limited.
[0005] In addition to the limitation of electrolyte wettability, the deficiency of the separator in flame retardancy also becomes the key to restrict the safety performance of the lithium ion battery. The traditional polyolefin separator is prone to thermal contraction and even melt collapse under high temperature environment, thereby losing the ability to isolate the positive and negative electrodes, leading to internal short circuit and further exacerbating the risk of thermal runaway. Therefore, researchers try to introduce high-temperature-resistant coating into the separator, such as ceramic coating, aramid resin coating, etc., to improve its thermal stability. However, even if some separators have certain high-temperature resistance, they do not have flame retardant function themselves when the battery is in thermal runaway, and it is difficult to truly achieve effective control of the internal heat spread of the battery.
[0006] Therefore, it is urgent to propose a new separator scheme that can balance electrolyte wettability and thermal stability, and also balance flame retardant function without significantly increasing manufacturing cost, thereby comprehensively improving the safety, cycle life and manufacturing efficiency of the lithium ion battery. SUMMARY
[0007] In view of the problems in the prior art, the purpose of the present application is to provide a composite separator and its manufacturing method and use, the composite separator comprising a hydrophilic modified separator matrix and a hydrophilic coating layer provided on the surface of the hydrophilic modified separator matrix; the components of the hydrophilic modified separator matrix include hydrophilically modified polyolefin; the components of the hydrophilic coating layer include specific modified composite fibers and aramid nanoparticles; the modified composite fibers include nanofibers wrapped with apatite nanowires, and the apatite nanowires are self-assembled and cross-linked hybridized on the nanofibers and form a network with pores. By selecting a hydrophilically modified separator matrix with high wettability and matching the surface with a self-assembled hybrid cross-linked composite fiber coating, the composite separator obtains excellent ion conductivity and electrolyte wettability; at the same time, the hydrophilic coating layer containing nanofibers wrapped with apatite nanowires also makes the composite separator have good heat resistance and flame retardancy.
[0008] To achieve this purpose, the present application adopts the following technical solutions:
[0009] In a first aspect, the present application provides a composite separator, comprising a hydrophilic modified separator matrix, and a hydrophilic coating layer provided on the surface of the hydrophilic modified separator matrix; the components of the hydrophilic modified separator matrix include hydrophilically modified polyolefin; the components of the hydrophilic coating layer include modified composite fibers and aramid nanoparticles; the modified composite fibers include nanofibers wrapped with apatite nanowires, and the apatite nanowires are self-assembled and cross-linked hybridized on the nanofibers by hydrogen bonding and van der Waals force, and form a network with pores.
[0010] The composite diaphragm modifies the conventional diaphragm substrate, so that the originally hydrophobic substrate becomes hydrophilic, and the wettability of the electrolyte is improved from the level of the substrate. By using a high-wetting hydrophilic modified diaphragm substrate, a specific hydrophilic coating layer is arranged on one side or both sides of the surface of the hydrophilic modified diaphragm substrate; the hydrophilic coating layer comprises modified composite fibers, including self-assembled hybrid cross-linked apatite nanowire wrapped nanofibers. The apatite nanowires themselves have a network structure, which is quickly self-assembled to form a cross-linked hybrid fiber network with hierarchical structure on the surface of the nanofibers through the interaction of hydrogen bonds and van der Waals forces, which is equivalent to hybrid modification of the nanofibers. The multi-level hierarchical composite hybrid fiber network makes the hydrophilic coating layer have the characteristics of rich pore structure, wide ion shuttle path, high specific surface area, high porosity and strong hydrophilicity, so that the composite diaphragm has excellent ion conductivity and electrolyte wettability, which can greatly shorten the liquid injection time, improve the efficiency of the battery cell manufacturing, solve the problems of liquid injection and excessive electrolyte, and also can supplement the liquid for the battery cell at the end of the cycle, improve the rapid decline of the service life of the diaphragm due to liquid shortage. At the same time, the apatite nanowires have flame retardant effect, so that the hydrophilic coating layer has good heat resistance and flame retardance, which can solve the problem of black leakage of the pole piece during the battery manufacturing process, and on the other hand, when the battery is subjected to external force impact, extrusion, overcharge and overheating, it can prevent the electrolyte from further burning and inhibit the spread of heat, thereby improving the safety of the battery.
[0011] The electrolyte suitable for the composite diaphragm described in the present application includes the electrolyte formula commonly used in the field of battery, for example, the common electrolyte includes solvent, lithium salt and additive; the solvent includes linear carbonate and / or cyclic carbonate, such as ethylene carbonate (EC), dimethyl carbonate (DMC), methyl ethyl carbonate (EMC) and the like; the lithium salt includes lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4) or lithium bis-trifluoromethanesulfonimide (LiTFSI) and the like, and the concentration of lithium salt is usually 0.8-1.4 mol / L; the additive includes vinylene carbonate (VC) or fluoroethylene carbonate (FEC) and the like.
[0012] The following is a preferred technical solution of the present application, but not as a limitation of the technical solutions provided by the present application, through the following technical solutions, the technical purpose and beneficial effects of the present application can be better achieved and realized.
[0013] Preferably, the thickness of the hydrophilic modified diaphragm substrate is 3-12 μm, for example 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm, etc.; the porosity is 30%-50%, for example 30%, 33%, 35%, 38%, 40%, 42%, 45%, 48% or 50%, etc.; the air permeability is 30-220 s / 100 cc, for example 30 s / 100 cc, 50 s / 100 cc, 80 s / 100 cc, 100 s / 100 cc, 120 s / 100 cc, 140 s / 100 cc, 160 s / 100 cc, 180 s / 100 cc, 200 s / 100 cc or 220 s / 100 cc, etc.; the electrolyte contact angle is 15°-20°, for example 15°, 16°, 17°, 18°, 19° or 20°, etc.; and the ionic conductivity is 0.95-1.85 mS / cm, for example 0.95 mS / cm, 0.98 mS / cm, 1 mS / cm, 1.2 mS / cm, 1.4 mS / cm, 1.6 mS / cm, 1.8 mS / cm or 1.85 mS / cm, etc.
[0014] Preferably, the polyolefin component of the hydrophilic modified polyolefin comprises PP and / or PE.
[0015] Preferably, the molecular weight of the PP is 200-1000 w, for example 200 w, 300 w, 400 w, 500 w, 600 w, 700 w, 800 w, 900 w or 1000 w, etc.; and the molecular weight of the PE is 300-2500 w, for example 300 w, 500 w, 800 w, 1000 w, 1200 w, 1400 w, 1600 w, 1800 w, 2000 w, 2200 w or 2500 w, etc.
[0016] Preferably, in the hydrophilic modified polyolefin, a hydrophilic functional group is introduced into the molecular chain of the polyolefin, and the hydrophilic functional group comprises at least one of a hydroxyl group, a carboxyl group or an amino group.
[0017] Preferably, the apatite nanowire comprises at least one of a hydroxyapatite nanowire, a hydroxyl carbonate apatite nanowire or a fluorapatite nanowire.
[0018] Preferably, the diameter of the apatite nanowire is 20-40 nm, for example 20 nm, 23 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm, 38 nm or 40 nm, etc.; and the length is 5-8 μm, for example 5 μm, 5.3 μm, 5.5 μm, 5.8 μm, 6 μm, 6.2 μm, 6.5 μm, 6.8 μm, 7 μm, 7.2 μm, 7.5 μm, 7.8 μm or 8 μm, etc.
[0019] Preferably, the nanofibers include cellulose nanofibers and aramid nanofibers.
[0020] In the present application, the nanofibers are preferably cellulose nanofibers and aramid nanofibers used in combination. The aramid nanofibers have good heat resistance, and the membrane formed by the aramid nanofibers has a high membrane breaking temperature, which can improve the safety of the battery cell. The combination of the two types of fibers can increase the drainage channels and accelerate the infiltration rate of the electrolyte.
[0021] Preferably, the cellulose nanofibers have a diameter of 300-600 nm, such as 300 nm, 330 nm, 350 nm, 380 nm, 400 nm, 420 nm, 450 nm, 480 nm, 500 nm, 520 nm, 550 nm, 580 nm, or 600 nm, etc., and a length of 20-30 μm, such as 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, or 30 μm, etc.; and the aramid nanofibers have a diameter of 350-800 nm, such as 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 630 nm, 650 nm, 700 nm, 750 nm, or 800 nm, etc., and a length of 30-40 μm, such as 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, or 40 μm, etc.
[0022] As a preferred technical solution of the present application, the aramid nanoparticles have a porous structure, and the pore size of the porous structure ranges from 18 nm to 46 nm, such as 18 nm, 20 nm, 24 nm, 26 nm, 28 nm, 30 nm, 33 nm, 35 nm, 38 nm, 40 nm, 42 nm, or 46 nm, etc.; and the particle size of the aramid nanoparticles ranges from 100 nm to 1000 nm, such as 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, or 1000 nm, etc.
[0023] In the present application, by adding a certain amount of aramid nanoparticles with a porous structure, line-to-line and point-to-line lapping are achieved, which can increase the electrolyte drainage channels and further accelerate the infiltration.
[0024] Preferably, the hydrophilic coating further includes a binder, a thickening agent, a wetting agent, and a dispersing agent.
[0025] Preferably, the binder includes an acrylic acid; the thickening agent includes carboxymethyl cellulose; the wetting agent includes at least one of a fatty alcohol, a polyether, and a siloxane; and the dispersing agent includes at least one of a polyacrylammonium salt and / or a polyacrylic acid sodium salt.
[0026] Preferably, the hydrophilic coating has a thickness of 0.5-3 μm, such as 0.5 μm, 0.85 μm, 1 μm, 1.3 μm, 1.5 μm, 1.85 μm, 2 μm, 2.3 μm, 2.5 μm, 2.8 μm or 3 μm, etc.; a porosity of 65%-72%, such as 65%, 66%, 67%, 68%, 69%, 70%, 71% or 72%, etc.; an air permeability value of 10-30 s / 100 cc, such as 10 s / 100 cc, 13 s / 100 cc, 15 s / 100 cc, 18 s / 100 cc, 20 s / 100 cc, 22 s / 100 cc, 25 s / 100 cc, 28 s / 100 cc or 30 s / 100 cc, etc.; and an ionic conductivity of 1.35-2.4 mS / cm, such as 1.35 mS / cm, 1.4 mS / cm, 1.5 mS / cm, 1.8 mS / cm, 2 mS / cm, 2.1 mS / cm, 2.3 mS / cm or 2.4 mS / cm, etc.
[0027] Preferably, the hydrophilic coating is arranged on one side surface or both side surfaces of the hydrophilically modified separator substrate.
[0028] Preferably, the composite separator has a total thickness of 3.5-18 μm, such as 3.5 μm, 5 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm or 18 μm, etc.
[0029] In a second aspect, the present application provides a method for manufacturing the composite separator of the first aspect, which comprises:
[0030] The apatite nanowires are mixed with the nanofibers in a liquid phase to perform a self-assembly reaction to obtain apatite nanowire-wrapped nanofibers; the apatite nanowire-wrapped nanofibers are formulated into a coating slurry with aramid nanoparticles to perform coating on the surface of the hydrophilically modified separator substrate to form a hydrophilic coating, thereby obtaining the composite separator.
[0031] As a preferred technical solution of the present application, the manufacturing method comprises: the nanofibers comprise cellulose nanofibers and aramid nanofibers; the apatite nanowires are formulated into a dispersion liquid X, the cellulose nanofibers are formulated into a dispersion liquid Y, and the aramid nanofibers are formulated into a dispersion liquid Z; the three dispersion liquids are mixed and stirred to perform a self-assembly reaction to obtain apatite nanowire-wrapped nanofibers.
[0032] Preferably, the self-assembly reaction has a temperature of 15-30℃, such as 15℃, 18℃, 20℃, 23℃, 25℃, 28℃ or 30℃, etc., and a time of 2-4 h, such as 2 h, 2.2 h, 2.5 h, 2.8 h, 3 h, 3.3 h, 3.5 h, 3.8 h or 4 h, etc.
[0033] Preferably, the concentration of the dispersion X is denoted as C, the diameter of the cellulose nanofiber is denoted as D a , the diameter of the aramid nanofiber is denoted as D b , then (0.4D a +0.6D b ) / 10≤C≤(0.4D a +0.6D b ) / 8.
[0034] To fully realize the composite modification of apatite to nanofiber, the required concentration of apatite nanowire needs to be proportional to the diameter of nanofiber. The larger the diameter of nanofiber, the higher the required concentration of apatite. Since the diameter of aramid nanofiber is larger than that of cellulose nanofiber, the coefficients before D a and D b in the relationship are defined as 0.4 and 0.6, respectively.
[0035] Preferably, the diameter of the apatite nanowire is 20-40 nm, such as 20 nm, 23 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm, 38 nm or 40 nm, etc.; and the length is 5-8 μm, such as 5 μm, 5.3 μm, 5.5 μm, 5.8 μm, 6 μm, 6.2 μm, 6.5 μm, 6.8 μm, 7 μm, 7.2 μm, 7.5 μm, 7.8 μm or 8 μm, etc.
[0036] Preferably, the diameter of the cellulose nanofiber is 300-600 nm, such as 300 nm, 330 nm, 350 nm, 380 nm, 400 nm, 420 nm, 450 nm, 480 nm, 500 nm, 520 nm, 550 nm, 580 nm or 600 nm, etc.; and the length is 20-30 μm, such as 20 μm, 22 μm, 24 μm, 26 μm, 28 μm or 30 μm, etc.; the diameter of the aramid nanofiber is 350-800 nm, such as 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 630 nm, 650 nm, 700 nm, 750 nm or 800 nm, etc.; and the length is 30-40 μm, such as 30 μm, 32 μm, 34 μm, 36 μm, 38 μm or 40 μm, etc.
[0037] Preferably, the concentration c of the dispersion liquid X is 25-100 mg / mL, such as 25 mg / mL, 35 mg / mL, 50 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL or 100 mg / mL, etc.; the concentration of the dispersion liquid Y is 10-18 mg / mL, such as 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL or 18 mg / mL, etc.; and the concentration of the dispersion liquid Z is 10-18 mg / mL, such as 10 mg / mL, 11 mg / mL, 12 mg / mL, 13 mg / mL, 14 mg / mL, 15 mg / mL, 16 mg / mL, 17 mg / mL or 18 mg / mL, etc.
[0038] Preferably, the amount of the dispersion liquid X accounts for 72%-80% of the total mass of the dispersion liquid X, the dispersion liquid Y and the dispersion liquid Z, such as 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79% or 80%, etc.; the amount of the dispersion liquid Y accounts for 10%-14%, such as 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5% or 14%, etc.; and the amount of the dispersion liquid Z accounts for 10%-14%, such as 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5% or 14%, etc.
[0039] As a preferred technical solution of the present application, the apatite nanowire includes at least one of hydroxyapatite nanowire, hydroxyapatite carbonate nanowire or fluorapatite nanowire.
[0040] Preferably, when the nanofiber wrapped with the apatite nanowire is formulated into a coating slurry with aramid nanoparticles, a binder, a thickener, a wetting agent and a dispersant are also added.
[0041] Preferably, the aramid nanoparticles have a porous structure, and the pore size of the porous structure ranges from 18 nm to 46 nm, such as 18 nm, 20 nm, 24 nm, 26 nm, 28 nm, 30 nm, 33 nm, 35 nm, 38 nm, 40 nm, 42 nm or 46 nm, etc.; and the particle size of the aramid nanoparticles ranges from 100 nm to 1000 nm, such as 100 nm, 200 nm, 300 nm, 500 nm, 600 nm, 800 nm, 900 nm or 1000 nm, etc.
[0042] Preferably, the binder comprises acrylic; the thickening agent comprises carboxymethyl cellulose; the wetting agent comprises at least one of fatty alcohols, polyethers and silicones; and the dispersing agent comprises at least one of polyacrylammonium salt and / or polyacrylic acid sodium salt.
[0043] Preferably, the total mass of the apatite nanowire-coated nanofiber, aramid nanoparticle, binder and thickening agent is 100%, and the proportion of the apatite nanowire-coated nanofiber is 47% to 76%, for example, 47%, 49%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 71%, 72%, 74% or 76%, etc.; the proportion of the aramid nanoparticle is 18% to 48%, for example, 18%, 23%, 25%, 28%, 30%, 33%, 35%, 38%, 40%, 42%, 45% or 48%, etc.; the proportion of the binder is 4.0% to 4.2%, for example, 4%, 4.02%, 4.06%, 4.1%, 4.13%, 4.15% or 4.2%, etc.; and the proportion of the thickening agent is 1.0% to 1.3%, for example, 1%, 1.03%, 1.06%, 1.09%, 1.16%, 1.18%, 1.23%, 1.26% or 1.3%, etc.
[0044] Preferably, the solvent in the coating slurry comprises water.
[0045] Preferably, the ratio of the total mass of the apatite nanowire-coated nanofiber, aramid nanoparticle, binder and thickening agent to the mass of the solvent is 24% to 30%, for example, 24%, 25%, 26%, 27%, 28%, 29% or 30%, etc.
[0046] Preferably, the wetting agent accounts for 0.3% to 0.6% of the total mass of the coating slurry, for example, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55% or 0.6%, etc.
[0047] Preferably, the dispersing agent accounts for 0.04% to 0.1% of the total mass of the coating slurry, for example, 0.04%, 0.05%, 0.06%, 0.07%, 0.08% or 0.1%, etc.
[0048] As a preferred technical solution of the present application, the method for preparing the hydrophilically modified diaphragm matrix comprises: mixing polyolefin raw material and hydrophilically modified raw material in a buffer solution, performing a modification reaction to obtain hydrophilically modified polyolefin; and performing wet extrusion film forming on the hydrophilically modified polyolefin to obtain a hydrophilically modified diaphragm matrix.
[0049] As a preferred technical scheme of the present application, the polyolefin raw material is first pre-cleaned, then mixed with the buffer solution, soaked, and mixed with the first hydrophilic modification raw material to perform a first hydrophilic modification reaction, and after the product is first cleaned, it is mixed with a solution containing a second hydrophilic modification raw material to perform a second hydrophilic modification reaction, and the product is second cleaned; the first hydrophilic modification reaction and the second hydrophilic modification reaction are alternately repeated to obtain a hydrophilic modified polyolefin.
[0050] Preferably, the polyolefin raw material includes PP powder and / or PE powder.
[0051] Preferably, the molecular weight of the PP powder is 200-1000 million, such as 200 million, 300 million, 400 million, 500 million, 600 million, 700 million, 800 million, 900 million or 1000 million, etc.; the molecular weight of the PE is 30-250 million, such as 30 million, 50 million, 80 million, 100 million, 120 million, 140 million, 160 million, 180 million, 200 million, 220 million or 250 million, etc.
[0052] Preferably, the cleaning solution for pre-cleaning includes ethanol.
[0053] Preferably, the buffer solution includes Tris-HCl buffer solution with a pH of 8.2-9.0.
[0054] Preferably, the soaking time is 5-8 min, such as 5 min, 5.5 min, 6 min, 6.5 min, 7 min, 7.5 min or 8 min, etc.
[0055] Preferably, the first hydrophilic modification raw material includes at least one of tannic acid, gallic acid or salicylic acid.
[0056] Preferably, the amount of the first hydrophilic modification raw material is 2.1-2.7 mg / mL, such as 2.1 mg / mL, 23.2 mg / mL, 2.3 mg / mL, 2.4 mg / mL, 2.5 mg / mL, 2.6 mg / mL or 2.7 mg / mL, etc.
[0057] Preferably, the second hydrophilic modification raw material includes at least one of polyethyleneimine, polyallylamine, poly(dimethylamino ethyl methacrylate) or chitosan.
[0058] Preferably, the amount of the second hydrophilic modification raw material is 0.8-1.3 mg / mL, such as 0.8 mg / mL, 0.9 mg / mL, 1 mg / mL, 1.1 mg / mL, 1.2 mg / mL or 1.3 mg / mL, etc.
[0059] Preferably, the cleaning solution for the first cleaning and the second cleaning includes water.
[0060] Preferably, the first hydrophilic modification reaction and the second hydrophilic modification reaction are performed for 20-30 minutes, such as 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes, or 30 minutes, etc.
[0061] Preferably, the number of times of the alternately repeating is at least 3.
[0062] Preferably, the wet extrusion film forming process comprises extrusion, casting, stretching, extraction, shaping, and winding.
[0063] In a third aspect, the present application provides a battery comprising the composite separator of the first aspect.
[0064] It should be noted that the present application does not specifically limit the specific type of battery to which the composite separator is applied, for example, the positive electrode material of the battery can be lithium iron phosphate or ternary positive electrode material; the battery can be prepared by winding process or laminating process.
[0065] It should also be noted that due to the limitation of the length and in order to avoid redundancy, the present application does not exhaustively list all the point values within the above numerical range, but also is not limited to the listed values, other unlisted values within the above numerical range are also applicable.
[0066] Compared with the prior art, the present application has at least the following beneficial effects:
[0067] The composite separator of the present application has excellent ion conductivity and electrolyte wettability by selecting a high-wetting hydrophilic modified separator substrate and a self-assembled hybrid cross-linked composite fiber coating on the surface, which can greatly shorten the liquid injection time, improve the efficiency of the battery cell manufacturing, solve the problems of liquid injection and excessive electrolyte, and also can supplement the liquid for the end-of-life cycle of the battery cell, improve the rapid decline of the service life of the separator due to liquid shortage. At the same time, the apatite nanowires have flame retardant effect, making the hydrophilic coating have good heat resistance and flame retardance, which can improve the problem of positive plate black leakage during battery cell manufacturing, and on the other hand, when the battery is subjected to external force impact, extrusion, overcharge and overheating, it can prevent the electrolyte from further burning, inhibit the spread of heat, and improve the safety of the battery. DETAILED DESCRIPTION
[0068] The technical solutions of the present application will be further described below through specific embodiments.
[0069] Those skilled in the art should understand that the embodiments are only to help understand the present application and should not be considered as specific limitations of the present application.
[0070] Example 1
[0071] The embodiment provides a composite diaphragm, which comprises a hydrophilic modified diaphragm substrate and a hydrophilic coating layer arranged on a surface of the hydrophilic modified diaphragm substrate.
[0072] The hydrophilic modified diaphragm substrate is composed of hydrophilic modified PE; the molecular weight of the PE component is 800,000-1,600,000, and the surface of the PE component has a hydrophilic functional group; and the thickness of the hydrophilic modified diaphragm substrate is 6.2 microns.
[0073] The hydrophilic coating layer comprises modified composite fibers, aramid nanoparticles, a binder, a thickening agent, a wetting agent and a dispersant.
[0074] The modified composite fibers comprise apatite nanowire-wrapped nanofibers, and the modified composite fibers form a network with pores by self-assembly cross-linking hybridization in the hydrophilic coating layer; the apatite nanowires are hydroxyapatite nanowires with a diameter of 34 nm and a length of 6.2 microns; the nanofibers are cellulose nanofibers and aramid nanofibers; the cellulose nanofibers have a diameter of 480 nm and a length of 26 microns; and the aramid nanofibers have a diameter of 580 nm and a length of 35 microns.
[0075] The aramid nanoparticles have a porous structure with a pore size range of 18-46 nm; the particle size of the aramid nanoparticles ranges from 100 nm to 1,000 nm; the binder comprises an acrylic acid; the thickening agent comprises carboxymethyl cellulose; the wetting agent comprises at least one of a fatty alcohol, a polyether and a siloxane; and the dispersant comprises at least one of polyacrylic acid ammonium salt and / or polyacrylic acid sodium salt.
[0076] The thickness of the hydrophilic coating layer is 1.6 microns, the hydrophilic coating layer is arranged on one side surface or double side surfaces of the hydrophilic modified diaphragm substrate, and the total thickness of the composite diaphragm is 9.4 microns.
[0077] The embodiment further provides a manufacturing method of the composite diaphragm, and the manufacturing method comprises the following steps.
[0078] S1. Preparing a hydrophilic modified diaphragm substrate with high wettability:
[0079] The polyolefin raw material PE powder with a molecular weight of 800-1600 is first pre-cleaned with ethanol, then soaked in Tris-HCl buffer solution with a pH of 8.2-9.0 for 5-8 min, then the first hydrophilic modification raw material tannic acid is added, and the amount of the first hydrophilic modification raw material is controlled to be 2.43 mg / mL for the first hydrophilic modification reaction; then the product is first cleaned with distilled water, and then soaked in an aqueous solution containing the second hydrophilic modification raw material polyethyleneimine, and the amount of the second hydrophilic modification raw material is controlled to be 1.1 mg / mL (and the concentration in the aqueous solution) for the second hydrophilic modification reaction for 26 min, and then the product is secondly cleaned with distilled water; the above process is repeated for 3 times to obtain the hydrophilic modified polyolefin; the above hydrophilic modified polyolefin is subjected to extrusion, casting, casting, stretching, extraction, shaping, winding and other processes based on the preparation process of a wet base film to obtain a hydrophilic modified diaphragm matrix.
[0080] S2. Preparation of coating slurry for hydrophilic coating:
[0081] Hydroxyapatite nanowires with a diameter of 34 nm and a length of 6.2 μm are provided; cellulose nanofibers with a diameter of D a = 480 nm and a length of 26 μm; aramid nanofibers with a diameter of D b = 520 nm and a length of 35 μm; an aqueous dispersion of hydroxyapatite nanowires X is prepared, and the concentration C of the aqueous dispersion X is 56 mg / mL, so that (0.4D a + 0.6D b ) / 9 = C; an aqueous dispersion Y of cellulose nanofibers and an aqueous dispersion Z of aramid fibers are respectively prepared, and the concentration of each is 14 mg / mL; the above three aqueous dispersions are mixed and self-assembled at room temperature for 3 h with a mass ratio of 7.6:1.2:1.2 to obtain modified composite fibers.
[0082] Subsequently, the above modified composite fibers, aramid nanoparticles, binder, thickener, wetting agent, dispersant are prepared into a coating slurry in water; the aramid nanoparticles are of a porous structure, and the ceramic particle size is 256 nm; the porous hole size on the surface of the particles is 28 nm; the binder is acrylic; the thickener is carboxymethyl cellulose; the wetting agent is a fatty alcohol; the dispersant is a polyacrylic acid sodium salt; wherein the mass ratio of the modified composite fibers, aramid nanoparticles, binder, thickener is 56.7:38:4.1:1.2, and the addition amount of the wetting agent and the dispersant accounts for 0.43% and 0.26% of the total weight of the entire coating slurry.
[0083] S3. Forming a hydrophilic coating:
[0084] The prepared coating slurry is coated on both sides of the hydrophilic modified separator substrate by water-based coating to form a hydrophilic coating, thereby obtaining a composite separator.
[0085] Example 2
[0086] In this example, the concentration C of the aqueous dispersion X of hydroxyapatite nanowires is adjusted from 56 mg / mL to 72 mg / mL in step S2 of the manufacturing method of the composite separator, such that (0.4D a + 0.6D b ) / 7 = C, and the other conditions are the same as in Example 1.
[0087] Example 3
[0088] In this example, the concentration C of the aqueous dispersion X of hydroxyapatite nanowires is adjusted from 56 mg / mL to 63 mg / mL in step S2 of the manufacturing method of the composite separator, such that (0.4D a + 0.6D b ) / 8 = C, and the other conditions are the same as in Example 1.
[0089] Example 4
[0090] In this example, the concentration C of the aqueous dispersion X of hydroxyapatite nanowires is adjusted from 56 mg / mL to 50.4 mg / mL in step S2 of the manufacturing method of the composite separator, such that (0.4D a + 0.6D b ) / 10 = C, and the other conditions are the same as in Example 1.
[0091] Example 5
[0092] In this example, the concentration C of the aqueous dispersion X of hydroxyapatite nanowires is adjusted from 56 mg / mL to 45.8 mg / mL in step S2 of the manufacturing method of the composite separator, such that (0.4D a + 0.6D b ) / 11 = C, and the other conditions are the same as in Example 1.
[0093] Example 6
[0094] In this example, the mass ratio of the modified composite fiber, aramid nanoparticles, binder, and thickening agent is adjusted from 56.7:38:4.1:1.2 to 39.1:55.6:4.1:1.2 in step S2 of the manufacturing method of the composite separator, and the other conditions are the same as in Example 1.
[0095] Example 7
[0096] This example provides a composite separator, in the manufacturing method step S2 of the composite separator, the mass ratio of modified composite fiber, aramid nanoparticles, binder, thickening agent is adjusted from 56.7:38:4.1:1.2 to 47.5:47.2:4.1:1.2, except the above, other conditions are exactly the same as example 1.
[0097] Example 8
[0098] This example provides a composite separator, in the manufacturing method step S2 of the composite separator, the mass ratio of modified composite fiber, aramid nanoparticles, binder, thickening agent is adjusted from 56.7:38:4.1:1.2 to 63.2:31.5:4.1:1.2, except the above, other conditions are exactly the same as example 1.
[0099] Example 9
[0100] This example provides a composite separator, in the manufacturing method step S2 of the composite separator, the mass ratio of modified composite fiber, aramid nanoparticles, binder, thickening agent is adjusted from 56.7:38:4.1:1.2 to 66.2:28.5:4.1:1.2, except the above, other conditions are exactly the same as example 1.
[0101] Comparative Example 1
[0102] This comparative example uses conventional unmodified PE powder with a molecular weight of 800,000-1,600,000, which is successively subjected to extrusion, casting, sheet casting, stretching, extraction, shaping, and winding processes to obtain a separator substrate. The separator substrate is subjected to subsequent testing. According to the manufacturing method steps S2 and S3 of example 1, a hydrophilic coating layer is formed on both sides of the separator substrate, but the coating layer does not contain the hydroxyapatite nanowires. Except the above, other conditions are exactly the same as example 1.
[0103] Comparative Example 2
[0104] This comparative example uses the separator substrate provided in comparative example 1, and according to the manufacturing method steps S2 and S3 of example 1, a hydrophilic coating layer is formed on both sides of the separator substrate, and the coating layer contains the hydroxyapatite nanowires. Except the above, other conditions are exactly the same as example 1.
[0105] Comparative Example 3
[0106] This comparative example uses the hydrophilic modified separator substrate obtained in step S1 of example 1 for subsequent testing, without performing steps S2 and S3, i.e., without setting a hydrophilic coating layer. Except the above, other conditions are exactly the same as example 1.
[0107] Characterization and testing:
[0108] I. The porosity, air permeability and ionic conductivity of the hydrophilic modified separator matrix in Example 1 and the separator matrix in Comparative Example 1 were tested, wherein: the porosity was tested using a PMI porosity analyzer; the air permeability was obtained by testing with a Curley instrument; and the ionic conductivity was obtained by making a button, testing the button with EIS, and fitting to calculate the ionic conductivity.
[0109] The porosity of the hydrophilic modified separator matrix in Example 1 was measured to be 41%, the air permeability was 178 s / 100 cc, and the ionic conductivity was 1.46 mS / cm. The porosity of the separator matrix in Comparative Example 1 was 38%, the air permeability was 175 s / 100 cc, and the ionic conductivity was 0.86 mS / cm.
[0110] The porosity and ionic conductivity of the hydrophilic coating obtained from Examples 1-9 and Comparative Example 2 were tested according to the above method, and the air permeability of the composite separator was tested to obtain the air permeability increment of the hydrophilic coating, and the results are shown in Table 1:
[0111] Table 1
[0112]
[0113]
[0114] Through analysis of the examples and comparative examples, the ionic conductivity of the separator prepared using the hydrophilically modified polyolefin raw material is significantly higher than that of the unmodified polyolefin raw material, because the hydrophilically modified base film has better wetting effect on the electrolyte and faster lithium ion transmission rate.
[0115] Comparing Comparative Example 1 with Comparative Example 2, it is found that the use of apatite nanowires has a greater impact on the conductivity and air permeability increment of the coating, because after self-assembly and cross-linking hybridization of the apatite nanowires, a network with rich pores is formed, the specific surface area of the coated nanofibers is increased, the electrolyte is wetted in the pores, and the ion conductivity and electrolyte wetting are improved.
[0116] Comparing Example 1 with Comparative Example 2, it is found that compared with the use of ordinary hydrophobic separators, the hydrophilic modified separator matrix has an effect on the hydrophilic coating. After the electrolyte is wetted in the coating, the wetting at the interface between the hydrophilic modified base film and the coating is fast, the conduction of lithium ions between the base film and the coating is accelerated, and the two can play a synergistic effect.
[0117] Comparing Example 1 with Examples 2-9 revealed that the dosage ratio of hydroxyapatite nanowires should be maintained within an appropriate range to fully leverage their self-assembly, cross-linking, and hybridization, achieving a complete and comprehensive coating of the nanofibers. Furthermore, the ratio of modified composite fibers to aramid nanoparticles in the hydrophilic coating also affects the coating's effectiveness. A greater proportion of modified composite fibers increases the porosity of the hydrophilic coating, while the increase in coating air permeability fluctuates between 10 and 30 s / 100 cc, with no significant difference.
[0118] II. The super-wettable flame-retardant separator proposed in this invention was subjected to the following tests: electrolyte contact angle, electrolyte wetting area, electrolyte absorption rate, thermal shrinkage at 180°C and 200°C, and flame retardancy testing. The electrolyte used in these tests contained EC, EMC, and DMC in a 3:3:4 volume ratio, and the lithium salt was LiPF6.
[0119] (1) Electrolyte contact angle test: Using the device LSA100, drop 5 μL of electrolyte (Taurus A60) on the diaphragm and read the contact angle after 10 seconds.
[0120] (2) Electrolyte wetting area test: Use the device LSA100 to drop 10 μL of electrolyte (Jinniu A60) on the diaphragm. After 30 seconds, the device calculates and reads the electrolyte wetting area.
[0121] (3) Electrolyte absorption rate test: 100×100mm 2 Place the single-sided diaphragm of different sizes in the electrolyte and soak it for 10 seconds. Then take it out and use a dust-free cloth to wipe off the excess electrolyte on the surface of the diaphragm. Calculate the electrolyte absorption rate by weighing.
[0122] (4) Thermal shrinkage test: First, measure the dimensions of each diaphragm sample in the MD (longitudinal) and TD (transverse) directions, which are recorded as L1 and H1 respectively; then bake the diaphragm at a certain temperature for 1 hour, and measure the dimensions in the MD and TD directions again, which are recorded as L2 and H2 respectively; the baking temperatures are 180℃ / 200℃ respectively; calculate the MD thermal shrinkage rate = (L1-L2) / L1×100%, and the TD thermal shrinkage rate = (H1-H2) / H1×100%.
[0123] (5) Flame retardant test: a flame ignition test is performed on the diaphragm in dry state and wet state (electrolyte is dripped on the surface of the diaphragm). The diaphragm is exposed to the flame to observe whether the diaphragm shrinks and is ignited;
[0124] The results are shown in Table 2.
[0125] Table 2
[0126]
[0127]
[0128] By analyzing the examples and comparative examples, the super-wetting flame-retardant separator provided by the present application has a heat shrinkage of <5% at 200°C, and has excellent heat shrinkage resistance. In a dry state, the separator does not shrink when the flame ignites the separator. In a wet state where the surface of the separator is wetted by electrolyte, the separator is not ignited, even if the electrolyte on the surface of the separator is ignited, the flame is immediately extinguished. In addition, the electrolyte contact angle of the separator of the example is close to 0°, the wetting area is large, and the electrolyte absorption rate is high, indicating that the separator has good wettability, strong liquid absorption and liquid retention capacity.
[0129] III. The separators obtained in the examples and comparative examples are assembled into batteries according to the following methods, respectively:
[0130] Step one, preparation of positive electrode sheet: a slurry is prepared by using lithium iron phosphate, conductive agent, binder, dispersant and NMP solvent, the slurry is coated on a carbon-coated aluminum foil and dried to obtain a positive electrode sheet, wherein the mass ratio of lithium iron phosphate, conductive agent, binder and dispersant is 96.8:1.25:1.85:0.1;
[0131] Step two, preparation of negative electrode sheet: a slurry is prepared by using artificial graphite, conductive agent, CMC thickening agent, SBR binder and water, the slurry is coated on a copper foil and dried to obtain a negative electrode sheet, wherein the mass ratio of artificial graphite, conductive agent, CMC thickening agent and SBR binder is 96.2:1.0:1.1:1.7;
[0132] Step three, the positive and negative electrode sheets and the separator are shaped by lamination or winding process to obtain a pole group. If the separator has a coating on only one side, the coating is on the positive electrode during lamination or winding. If the separator has a coating on both sides, the positive and negative electrodes are not distinguished. Then, the pole group is heat pressed to obtain a pole group with a certain hardness;
[0133] Step four, packaging, baking and liquid injection: the prepared pole group is packaged in a square shell, the packaged battery cell is placed in an oven and baked at 95±5°C for 10±3h, and then electrolyte is injected;
[0134] Step five, pre-charging and formation: after standing, the battery cell is pre-charged, formed and separated, i.e. the battery is prepared.
[0135] In the process of preparing the battery, the injection time is recorded, i.e. the total time from the start of injection to the end of injection, and the weight of the free electrolyte after full charging and disassembly. The battery is tested for 25°C / 45°C cycle test, limit heat box, room temperature and 60°C heat spread test. The results are shown in Table 3.
[0136] Table 3
[0137]
[0138]
[0139] Through the analysis of examples and comparative examples, the battery prepared by the example separator can greatly shorten the liquid injection time and improve the battery cell manufacturing efficiency. After full charging, there is less free electrolyte, which shows that the liquid retention capacity is strong, and the electrolyte is supplemented in the later stage of the cycle to improve the cycle life of the battery cell. From the cycle data, it can be seen that the capacity retention rate of the example separator at 25 DEG C and 45 DEG C is optimal. It can pass the 250 DEG C limit heat box test, and the battery cell does not occur heat spread at normal temperature and 60 DEG C. In the comparative examples, the injection time is longer, and there is more free electrolyte after full charging and disassembly, the wettability is poor, and then the battery cycle life is affected. In comparative example 1 and comparative example 3, the separator without adding hydroxyapatite is affected by heat resistance and flame retardance, and the safety performance of the corresponding battery cell is the worst.
[0140] As can be seen from the above, the composite separator proposed in the present application has excellent electrolyte wettability, improves the liquid absorption and liquid retention capacity, can greatly shorten the battery liquid injection time, improve the manufacturing efficiency, solve the liquid injection problem, and can supplement the electrolyte in the later stage of the battery cycle to avoid the phenomenon of liquid depletion on the large surface of the battery cell, and improve the cycle life of the battery cell. The separator proposed in the present application has excellent heat resistance and flame retardance at the same time, the heat shrinkage is less than 5% at 200 DEG C, and the dry and wet state of the separator cannot be ignited by the flame. When the battery is in thermal runaway, the separator can inhibit the combustion of electrolyte and active material, and still plays a role in isolating the positive and negative electrodes, and inhibiting heat spread. The battery proposed in the present application can pass the 250 DEG C limit heat box, and the heat spread test at normal temperature and 60 DEG C.
[0141] The preferred embodiments of the present application are described in detail above, but the present application is not limited to the specific details in the above embodiments, and various simple modifications can be made to the technical solutions of the present application within the technical concept of the present application, and these simple modifications all belong to the protection scope of the present application.
[0142] In addition, it should be noted that various specific technical features described in the above specific embodiments can be combined in any appropriate manner without contradiction, and in order to avoid unnecessary repetition, various possible combinations are not described again in the present application.
[0143] In addition, various different embodiments of the present application can also be combined in any manner, as long as it does not deviate from the idea of the present application, and it should also be considered as disclosed in the present application.
Claims
1. A composite separator, characterized by, The composite diaphragm comprises a hydrophilic modified diaphragm base and a hydrophilic coating layer arranged on the surface of the hydrophilic modified diaphragm base; the components of the hydrophilic modified diaphragm base comprise a hydrophilic modified polyolefin; the components of the hydrophilic coating layer comprise modified composite fibers and aramid nanoparticles; the modified composite fibers comprise nanofibers wrapped with apatite nanowires, the apatite nanowires are self-assembled and cross-linked on the nanofibers by hydrogen bonds and van der Waals forces, and form a network with pores.
2. The composite separator of claim 1, wherein The thickness of the hydrophilic modified diaphragm base is 3-12 microns, the porosity is 30%-50%, the air permeability is 30-220 s / 100cc, the electrolyte contact angle is 15-20 degrees, and the ionic conductivity is 0.95-1.85 mS / cm; Preferably, the polyolefin component in the hydrophilic modified polyolefin comprises PP and / or PE; Preferably, the molecular weight of the PP is 200-1000 thousand; the molecular weight of the PE is 300-2500 thousand; Preferably, in the hydrophilic modified polyolefin, a hydrophilic functional group is introduced on the molecular chain of the polyolefin, and the hydrophilic functional group comprises at least one of a hydroxyl group, a carboxyl group or an amino group.
3. The composite separator according to claim 1 or 2, characterized in that, The apatite nanowires comprise at least one of hydroxyapatite nanowires, hydroxyapatite carbonate nanowires or fluorapatite nanowires; Preferably, the diameter of the apatite nanowires is 20-40 nm, and the length is 5-8 microns; Preferably, the nanofibers comprise cellulose nanofibers and aramid nanofibers; Preferably, the diameter of the cellulose nanofibers is 300-600 nm, and the length is 20-30 microns; the diameter of the aramid nanofibers is 350-800 nm, and the length is 30-40 microns.
4. The composite separator according to any one of claims 1 to 3, wherein The aramid nanoparticles have a porous structure, and the pore size of the porous structure ranges from 18 to 46 nm; the particle size of the aramid nanoparticles ranges from 100 to 1000 nm; Preferably, the hydrophilic coating layer further comprises a binder, a thickening agent, a wetting agent and a dispersant; Preferably, the binder comprises an acrylic acid; the thickening agent comprises carboxymethyl cellulose; the wetting agent comprises at least one of a fatty alcohol, a polyether and a siloxane; and the dispersant comprises at least one of a polyacrylic acid ammonium salt and / or a polyacrylic acid sodium salt; Preferably, the thickness of the hydrophilic coating layer is 0.5-3 microns, the porosity is 65%-72%, the air permeability value is 10-30 s / 100cc, and the ionic conductivity is 1.35-2.4 mS / cm; Preferably, the hydrophilic coating layer is arranged on one side surface or both side surfaces of the hydrophilic modified diaphragm base; Preferably, the total thickness of the composite diaphragm is 3.5-18 microns.
5. A method of producing the composite separator as claimed in any one of claims 1 to 4, characterized by, The manufacturing method comprises: Mixing apatite nanowires and nanofibers in a liquid phase to perform a self-assembly reaction to obtain nanofibers wrapped with apatite nanowires; preparing the nanofibers wrapped with apatite nanowires and aramid nanoparticles into a coating slurry to perform coating on the surface of the hydrophilic modified diaphragm base to form a hydrophilic coating layer, thereby obtaining a composite diaphragm.
6. The method of claim 5, wherein The manufacturing method comprises that: the nanofiber comprises cellulose nanofiber and aramid nanofiber; the apatite nanowire is prepared into a dispersion liquid X, the cellulose nanofiber is prepared into a dispersion liquid Y, the aramid nanofiber is prepared into a dispersion liquid Z, the three dispersion liquids are mixed and stirred, a self-assembly reaction is carried out, and the apatite nanowire wrapped nanofiber is obtained; Preferably, the temperature of the self-assembly reaction is 15-30℃, and the time is 2-4h; Preferably, the concentration of said dispersion X is noted C, the diameter of said cellulose nanofiber is noted D a , the diameter of said aramid nanofiber is noted D b , then (0.4D a + 0.6D b ) / 10 ≤ C ≤ (0.4D a + 0.6D b ) / 8; Preferably, the diameter of the apatite nanowire is 20-40nm, and the length is 5-8μm; Preferably, the cellulose nanofiber has a diameter D a of 300-600 nm and a length of 20-30 μm; and the aramid nanofiber has a diameter D b of 350-800 nm and a length of 30-40 μm. Preferably, the concentration C of the dispersion liquid X is 25-100mg / mL, the concentration of the dispersion liquid Y is 10-18mg / mL, and the concentration of the dispersion liquid Z is 10-18mg / mL; Preferably, according to the total mass of the dispersion liquid X, the dispersion liquid Y and the dispersion liquid Z being 100%, the amount of the dispersion liquid X accounts for 72%-80%, the amount of the dispersion liquid Y accounts for 10%-14%, and the amount of the dispersion liquid Z accounts for 10%-14%.
7. The method of manufacturing a composite separator according to claim 5 or 6, characterized by, The apatite nanowire comprises at least one of hydroxyapatite nanowire, hydroxy carbonate apatite nanowire or fluorapatite nanowire; Preferably, when the apatite nanowire wrapped nanofiber is prepared into a coating slurry together with aramid nano-particles, a binder, a thickening agent, a wetting agent and a dispersant are further added; Preferably, the aramid nano-particles have a porous structure, and the pore size of the porous structure ranges from 18nm to 46nm; the particle size of the aramid nano-particles ranges from 100nm to 1000nm; Preferably, the binder comprises acrylic acid; the thickening agent comprises carboxymethyl cellulose; the wetting agent comprises at least one of fatty alcohol, polyether and siloxane; and the dispersant comprises at least one of polyacrylammonium salt and / or polyacrylic acid sodium salt; Preferably, according to the total mass of the apatite nanowire wrapped nanofiber, the aramid nano-particles, the binder and the thickening agent being 100%, the apatite nanowire wrapped nanofiber accounts for 47%-76%, the aramid nano-particles accounts for 18%-48%, the binder accounts for 4.0%-4.2%, and the thickening agent accounts for 1.0%-1.3%; Preferably, the solvent in the coating slurry comprises water; Preferably, the mass ratio of the total mass of the apatite nanowire wrapped nanofiber, the aramid nano-particles, the binder and the thickening agent to the mass of the solvent is 24%-30%; Preferably, the wetting agent accounts for 0.3%-0.6% of the total mass of the coating slurry; Preferably, the dispersant accounts for 0.04%-0.1% of the total mass of the coating slurry.
8. The method of claim 5-7, wherein The method for preparing the hydrophilic modified diaphragm matrix comprises: mixing polyolefin raw material and hydrophilic modification raw material in a buffer solution, carrying out a hydrophilic modification reaction to obtain hydrophilic modified polyolefin, and carrying out wet extrusion film forming on the hydrophilic modified polyolefin to obtain a hydrophilic modified diaphragm matrix.
9. The method of claim 8, wherein the step of forming the composite separator is performed by a method selected from the group consisting of a co-extrusion method, a lamination method, and a coating method. The polyolefin raw material is pre-cleaned, mixed with the buffer solution, soaked, mixed with the first hydrophilic modification raw material, and then the first hydrophilic modification reaction is carried out. After the first cleaning of the product, the product is mixed with a solution containing the second hydrophilic modification raw material, and then the second hydrophilic modification reaction is carried out. After the second cleaning of the product, the first hydrophilic modification reaction and the second hydrophilic modification reaction are alternately repeated to obtain the hydrophilic modified polyolefin. Preferably, the polyolefin raw material comprises PP powder and / or PE powder. Preferably, the molecular weight of the PP powder is 200-1000 million; and the molecular weight of the PE powder is 300-2500 million. Preferably, the cleaning solution for the pre-cleaning comprises ethanol. Preferably, the buffer solution comprises Tris-HCl buffer solution with pH of 8.2-9.
0. Preferably, the soaking time is 5-8 min. Preferably, the first hydrophilic modification raw material comprises at least one of tannic acid, gallic acid or salicylic acid. Preferably, the amount of the first hydrophilic modification raw material is 2.1-2.7 mg / mL. Preferably, the second hydrophilic modification raw material comprises at least one of polyethyleneimine, polyallylamine, poly(dimethylamino ethyl methacrylate) or chitosan. Preferably, the amount of the second hydrophilic modification raw material is 0.8-1.3 mg / mL. Preferably, the cleaning solution for the first cleaning and the second cleaning comprises water. Preferably, the time for the first hydrophilic modification reaction and the second hydrophilic modification reaction is 20-30 min. Preferably, the number of the alternately repeated times is at least 3. Preferably, the process of the wet extrusion film forming comprises extrusion, casting, sheet casting, stretching, extraction, setting and winding.
10. A battery, characterized by The composite separator comprises the composite separator according to any one of claims 1-4.
